THE LAST ICE PHOENIX - Reyes, Megan (New York : Random House Children's Books, 2024)
Realizing their destinies as saviors, Blue, River, Shenli, and Wren grapple with their roles and expectations, and as they embark on separate quests amidst looming war, they navigate individual challenges, choices, and revelations in their quest to decipher the Fates' plan for them
Ages 8-12
Keywords: Magic -- Juvenile fiction; Dragons -- Juvenile fiction; Prophecies -- Juvenile fiction; Fantasy fiction